Palm Acupressure: A Complementary Intervention to Accelerate the Progression of the First Stage of Active Labour in Primigravida - wandari, setia; Setiawandari, Setiawandari; Iswati, Retno Setyo; Sulistyowati, Dwi (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2026)
The success of labour is influenced by optimal labour progress during the active stage, characterised by accelerated cervical dilation. The active stage of labour is the longest phase and a critical period determining the success of a normal delivery. If labour progresses more slowly than expected, it can potentially lead to complications for the mother and baby. The purpose of this study was to analyse the effect of palm acupressure on the duration of the active stage of labour. The research method used a true experiment with a two-group pre-test post-test control design. Fifty-eight primigravida subjects giving birth at RSPAL Dr Ramelan in Surabaya were divided into two groups. The intervention group received palm acupressure, while the control group received deep breathing relaxation. Labour duration was monitored using a partograph. The independent t-test showed a p-value of 0.041, indicating a difference in labour duration between the two groups. The average difference in labour duration was 1 hour and 43 minutes. In conclusion, palm acupressure affects the duration of the active stage of labour. This intervention has the potential to prevent prolongation of the first stage and can be used as an alternative to strengthen uterine contractions in cases of labour with contraction disorders